Emerging Exosomes and Exosomal MiRNAs in Spinal Cord Injury - Feng, Jia; Zhang, Yifan; Zhu, Zhihan; Gu, Chenyang; Waqas, Ahmed; Chen, Lukui (Frontiers in Cell and Developmental Biology, 2021)
Acute spinal cord injury (SCI) is a serious traumatic event to the spinal cord with considerable morbidity and mortality. This injury leads to short- and long-term variations in the spinal cord, and can have a serious effect on the patient’s sensory, motor, or autonomic functions. Due to the complicated pathological process of SCI, there is currently no successful clinical treatment strategy. Exosomes, extracellular vesicles (EVs) with a double-layer membrane structure of 30–150 nm diameter, have recently been considered as critical mediators for communication between cells and tissues by transferring proteins, lipids, and nucleic acids. Further studies verified that exosomes participate in the pathophysiological process of several diseases, including cancer, neurodegenerative diseases, and cardiovascular diseases, and could have a significant impact in their treatment. As natural carriers of biologically active cargos, exosomes have emerged as pathological mediators of SCI. In this review article, we critically discuss the functions of exosomes as intracellular mediators and potential treatments in SCI and provide an outlook on future research.